(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: Conflict and conflict resolution are as old as humanity. At different ages, people try to remedy conflicts between individuals or groups in different ways. The sending of ambassadors or the court of the king’s bench, as an institution of arbitration, or even the archaic form of mediation, can be found in thousands of years of historical sources. In this study, the focus is exploring the aforementioned processes. Methodology: In this paper, we follow alternative dispute resolution methods from the ancient Greeks’ conflict management tools to the development of modern mediation and the EU legal harmonization. Methodologically, we used the processing and comparison of contemporary sources. Findings: In both Hungarian and European cultures, there is a tradition of a type of mediation process. In several European cultures, this can still be felt. Value: This article highlights the fact that the third neutral party’s presence in the interpersonal dispute resolution is an archaic human need. Its role is inevitable in everyday (alternative) dispute resolution.